Educational practices in higher education: traditional versus open - Abakumova, Natalia N. (Вестник Томского государственного университета)
The article actualizes the problem of educational practices transformation in universities. The factors and stages of educational practices development are established. The analysis of Russian and foreign experience of open educational practices implementation in universities is conducted. The characteristics allowing to make a comparative analysis of traditional and open educational practices are defined. The conclusion is made about the primacy of traditional educational practices, which ensure the necessary competencies` for working with open educational practices.